Pengaruh Kebijakan Dividen, Kebijakan Hutang, dan Profitabilitas terhadap Nilai Perusahaan Sektor Makanan dan Minuman yang Terdaftar pada Bursa Efek Indonesia (BEI) Tahun 2020-2023 - Risna Widya Rachmanila; Badrus Zaman; Diah Nurdiwaty (STIKes Ibnu Sina Ajibarang, 2024)
This study is based on the fact that company value is very important for the sustainability of the company. The purpose of this study is to examine the effect of dividend policy, debt policy, and profitability on the value of food and beverage sector companies listed on the Indonesia Stock Exchange (IDX) in 2020-2023. This study uses a descriptive quantitative approach. The population in this study were food and beverage companies listed on the Indonesia Stock Exchange (IDX) in 2020-2023. The sampling technique used the Purposive Sampling method and the resulting sample included 22 food and beverage sector companies. The conclusion of the research results shows that partially dividend policy affects company value with a significance value of 0.031 <0.05. Debt policy has a partial effect on company value with a significance value of 0.012 <0.05, while profitability does not affect company value with a significance value of 0.315 <0.05. The results of the study also show that simultaneously, dividend policy, debt policy, and profitability have a significant effect on company value with a significance value of the F test of 0.017.